Optical pressure sensing in vacuum and high-pressure ranges using lanthanide-based luminescent thermometer–manometer. Issue 13 (23rd March 2021) - Runowski, Marcin; Woźny, Przemysław; Martín, Inocencio R.
Abstract : Luminescent thermometer–manometer working as a low (vacuum) and high pressure sensor. Abstract : Pressure is a fundamental physical parameter, so its monitoring is crucial for various industrial and scientific purposes. However, the available optical sensors allow monitoring in either low pressure or high pressure ranges. In this work, different concepts of pressure sensing are combined, and the first luminescent pressure sensor working within 9-orders of magnitude (from 10 −4 to 10 5 bar) is developed, allowing both low (vacuum) and high pressure sensing. This sensor is based on the inorganic, upconverting material (YPO4 :Yb 3+ –Er 3+ ) emitting in the visible and near-infrared (NIR) ranges. For vacuum detection, the recently discovered sensing method is applied, which is based on the conversion of a luminescent thermometer into the pressure sensor. This is because of the effect of light-to-heat conversion, which is greatly enhanced under vacuum conditions, and manifested as a change in the intensity ratio of Er 3+ thermally-coupled bands (525/550 nm). Whereas for high-pressure sensing, the emission line shift of Er 3+ (induced by materials compression), located in the NIR spectral range, is used.